Fluorescence lifetime imaging of NAD(P)H upon oxidative stress in Kluyveromyces marxianus - Ai, Yi; Luo, Ruoyu; Yang, Deqiang; Ma, Jiong; Yu, Yao; Lu, Hong (Frontiers in Bioengineering and Biotechnology, 2022)
Kluyveromyces marxianus is a promising cell factory for producing heterologous proteins. Oxidative stresses were raised during overexpression of heterologous proteins, leading to the shift of the redox state. How to measure the redox state of live K. marxianus cells without perturbing their growth remains a big challenge. Here, a fluorescence lifetime imaging (FLIM)-based method was developed in live K. marxianus cells. During the early exponential growth, K. marxianus cells exhibited an increased mean fluorescence lifetime (τ-mean) of NAD(P)H compared with Saccharomyces cerevisiae cells, which was consistent with the preference for respiration in K. marxianus cells and that for fermentation in S. cerevisiae cells. Upon oxidative stresses induced by high temperature or H2O2, K. marxianus cells exhibited an increased τ-mean in company with decreased intracellular NAD(P)H/NAD(P)+, suggesting a correlation between an increased τ-mean and a more oxidized redox state. The relationship between τ-mean and the expression level of a heterologous protein was investigated. There was no difference between the τ-means of K. marxianus strains which were not producing a heterologous protein. The τ-mean of a strain yielding a high level of a heterologous protein was higher than that of a low-yielding strain. The results suggested the potential application of FLIM in the non-invasive screen of high-yielding cells.